A Determinants of Financial Performance and Their Impact on Firm Value in the Building Construction Industry Sub-Sector - M. Noor Salim; Sudjono Sudjono; Suratno Suratno (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
This study aims to analyze the effect of intellectual capital, managerial ownership, company size and company financial performance on firm value. This research was conducted at building construction industry sub-sector companies listed on the Indonesia Stock Exchange for the observation period from 2017 – 2021. A total sample of 9 companies was obtained using a purposive sampling technique. This study used panel data regression analysis with STATA 17 software. The results showed that intellectual capital had a positive and significant effect on the company's financial performance, while managerial ownership and company size had a negative and significant effect. Intellectual capital has a positive and insignificant effect on firm value, while managerial ownership and firm size have a negative and significant effect. The company's financial performance has a positive and significant effect on firm value, and is able to mediate the influence of intellectual capital on firm value. However, the company's financial performance is not able to mediate the effect of managerial ownership and company size on firm value. This research will have an impact on increasing understanding and consideration for investors when making decisions to invest in the Indonesian Stock Exchange.